Why do military regimes institutionalize?: constitution-making and elections as political survival strategy in Myanmar - Croissant, Aurel; Kamerling, Jil (Asian journal of political science, 2013)
In recent years Myanmar underwent drastic political changes. While many see these changes as first tentative steps towards democratization, we argue that the current political transformation is not a deliberate process of liberalization, but a survival strategy of the military regime. Using arguments of the ‘new institutionalism’ as a theoretical foundation, this article explores the hypothesis that the high degree of professionalization of the Burmese military creates the incentive to institutionalize power-sharing among the ruling elite. Our empirical analysis finds evidence for both a highly professionalized military and institutions that by securing the military's continuing dominance serve the purpose of institutionalizing military power- sharing. These results imply that further democratization is unlikely as it must be initiated from within the still dominating military itself.
Gesehen am 27.07.2017